Stress Predictors in Nursing Students during the COVID-19 Pandemic Confinement - Lourenço, Tânia (2022)
Background: The COVID-19 pandemic has largely impacted nursing education. Owing to the element of confinement, emergency education fostered conflicts between problems and their solutions, leading to higher stress among students. Objective: The aim of the study was to identify the determinants of perceived stress in nursing students during confinement due to the COVID-19 pandemic. Methods: This multicentric, quantitative, and cross-sectional study employed the multiple linear regression model. The study was conducted at seven nursing graduate schools in the Iberian Peninsula, with 1,058 nursing graduate students in confinement. An online questionnaire was administered to nursing students between April 23 rd and May 02 nd , 2020. According to socio-demographic data, COVID-19 experience, satisfaction with learning strategies, and coping strategies ( Brief COPE scale ) of the nursing students, the model was developed with the Perceived Stress Scale as the explained variable. Results: Stress is predictable in the form of greater coping-avoidance (b = 2.415; p < .001) when a family member is infected (b = -2.354; p = .005) and in younger students (b = -.104; p = .002). It tends to be lower with higher coping-reflective (b = -2.365; p < .001) and when the students have a more favourable self-perceived life (b = -1.206; p < .001). Furthermore, the stress has been found to be higher in Portuguese students (b = -1.532; p < .001) and women (b = 2.276; p < .001) than their Spain and male counterparts, respectively. Among variables related to academics, perceived stress is higher when the students are dissatisfied with the time spent on the computer (b = 1.938) and with the evaluation methods (b = 1.448). Conclusion: Personal factors and the ease of mobilisation of the proposed training strategies affect the students’ ability to deal with stress. Emergency education should consider stress predictors so that the students can adapt to training better.